Triple Band Mime Antenna for Modern Commercial Applications (International Journal of Innovative Research in Computer Science & Technology, 2022)
The article presents the analysis and  design of MIMO monopoly Antenna along with split ring  resonator to get frequency notch characteristic in the wide  band. Frequency notch characteristics are achieved by  keeping the split ring resonators on one side of the  substrate and on the back of the substrate at deficient  ground structure a complementary split Ring resonator  with respect to microstrip feeding. Between 2.5-9.5GHz  and 12.548-20GHz the dual notch band characteristics are  acquired. The inspected conformal characteristics of the  antenna hold eminent unceasing reflection coefficient  characteristics at different angles in the overall band.  Analyzed the unit cell of the SRR and also examined the  antenna impedance and radiation characteristics of the  model.
Keywords: Band Notch; Rectangular Monopoly; Complementary Split Ring Resonator (CSRR) Detected Ground Structure (DGS; Split Ring Resonator (SRR)